2009
DOI: 10.5194/bg-6-2611-2009
|View full text |Cite
|
Sign up to set email alerts
|

From laboratory manipulations to Earth system models: scaling calcification impacts of ocean acidification

Abstract: Abstract. The observed variation in the calcification responses of coccolithophores to changes in carbonate chemistry paints a highly incoherent picture, particularly for the most commonly cultured "species", Emiliania huxleyi. The disparity between magnitude and potentially even sign of the calcification change under simulated end-of-century ocean surface chemical changes (higher pCO 2 , lower pH and carbonate saturation), raises challenges to quantifying future carbon cycle impacts and feedbacks because it i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
161
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 62 publications
4
161
0
Order By: Relevance
“…These results are in contrast with those of earlier studies examining the combined effects of elevated pCO 2 and temperature: one study found decreased PIC content in the same strain (CCMP371) [23], and two studies found no change in PIC content in different strains (RCC1228 and PML B92/11) [18,22] (table 6). Responses of calcification to elevated pCO 2 are known to vary across strains of E. huxleyi [7,8,15], and responses to the combination of elevated pCO 2 and temperature could also be strain-specific. Therefore, a strain-specific response could explain some of the different results in the experiments under elevated pCO 2 and temperature, but not the different response of the same strain (CCMP 371) [7,8,23].…”
Section: Discussion (A) Inorganic Carbon Physiologymentioning
confidence: 99%
See 4 more Smart Citations
“…These results are in contrast with those of earlier studies examining the combined effects of elevated pCO 2 and temperature: one study found decreased PIC content in the same strain (CCMP371) [23], and two studies found no change in PIC content in different strains (RCC1228 and PML B92/11) [18,22] (table 6). Responses of calcification to elevated pCO 2 are known to vary across strains of E. huxleyi [7,8,15], and responses to the combination of elevated pCO 2 and temperature could also be strain-specific. Therefore, a strain-specific response could explain some of the different results in the experiments under elevated pCO 2 and temperature, but not the different response of the same strain (CCMP 371) [7,8,23].…”
Section: Discussion (A) Inorganic Carbon Physiologymentioning
confidence: 99%
“…Responses of calcification to elevated pCO 2 are known to vary across strains of E. huxleyi [7,8,15], and responses to the combination of elevated pCO 2 and temperature could also be strain-specific. Therefore, a strain-specific response could explain some of the different results in the experiments under elevated pCO 2 and temperature, but not the different response of the same strain (CCMP 371) [7,8,23].…”
Section: Discussion (A) Inorganic Carbon Physiologymentioning
confidence: 99%
See 3 more Smart Citations